1990
DOI: 10.1111/j.1365-2648.1990.tb01740.x
|View full text |Cite
|
Sign up to set email alerts
|

Fostering hope in terminally‐ill people

Abstract: This study explored the meaning of hope and identified strategies that are used to foster hope in a convenience sample of 30 terminally-ill adults using the technique of methodological triangulation (interview, Herth Hope Index and Background Data Form). Cross-sectional data were collected on 20 of the subjects, and longitudinal data were collected on 10 of the subjects in order to provide a clearer understanding of the hoping process during the dying trajectory. Hope was defined as an inner power directed tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
302
1
20

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 381 publications
(348 citation statements)
references
References 19 publications
25
302
1
20
Order By: Relevance
“…Tam naudojamos atitinkamos strategijos: kontakto užmezgimas bei palaikymas, slaugytojo požiūris į slaugos darbą ir pan. (Herth, 1990;. Didesnę viltį išgyvenantys slaugytojai, dirbantys su sunkiai sergančiais pacientais, jaučiasi geriau (Feudtner ir kt., 2007).…”
Section: Viltis Slaugojeunclassified
“…Tam naudojamos atitinkamos strategijos: kontakto užmezgimas bei palaikymas, slaugytojo požiūris į slaugos darbą ir pan. (Herth, 1990;. Didesnę viltį išgyvenantys slaugytojai, dirbantys su sunkiai sergančiais pacientais, jaučiasi geriau (Feudtner ir kt., 2007).…”
Section: Viltis Slaugojeunclassified
“…From interviews with terminally ill patients, Herth (1990) identified the hope fostering importance of humour, good memories, positive affirmation and belief in God. A belief in God helped to provide a sense of meaning for their suffering.…”
Section: The Experience Of Hope In Different Contextsmentioning
confidence: 99%
“…It is increasing suggested that nurses are an important source of hope for people who are vulnerable and ill (Herth 1990, Stephenson 1991, Herth 1996, Cutcliffe & Grant 2001, Moore 2005; due to their constant interaction with patients who are suffering.…”
Section: The Contribution Of Nursing and The Relevance Of Hope To CLImentioning
confidence: 99%
See 2 more Smart Citations